Endobronchial Ultrasound And Transbronchial Needle Aspiration Ebus-Tbna: Experience In Fundacion Valle Del Lili, A University Hospital Of Reference In Latin America (2016)
Endobronchial Ultrasound and Transbronchial Needle Aspiration (EBUS-TBNA) is a minimally invasive technique, will tolerated, cost efficient, for real time visualization of the airways with ultrasound and for sampling the mediastinum and hilum, its indications: diagnosis, staging, restaging of lung cancer, evaluation of metastatic lesions and non malignant diseases. It requires multidisciplinary evaluation with image analysis, general condition of the patient, risks and benefits, also close work with pathology, performing a Rapid On Site Evaluation (ROSE) to improve the diagnostic performance. Objective: To describe the experience with EBUS-TBNA in Fundación Valle del Lili (FVL).